Sensory co‐evolution: The sex attractant of a gall‐making fly primes plant defences, but female flies recognize resulting changes in host‐plant quality. (8th July 2020) - Yip, Eric C.; De Moraes, Consuelo M.; Tooker, John F.; Mescher, Mark C.
Abstract: Tall goldenrod plants Solidago altissima appear to eavesdrop on the communication of a specialist gall‐inducing fly Eurosta solidaginis by detecting the volatile emissions of male flies and priming anti‐herbivore defences. However, the effects of defence priming on fly fitness have not previously been demonstrated, despite some evidence that female flies avoid ovipositing on primed plants in the field. To explore how priming affects female preferences and galling success, we manipulated exposure to the priming cue in multiple genotypes of S. altissima and assessed rates of oviposition and gall development. Priming reduced gall formation overall; however, its effect varied across plant genotypes, as well as by the age of the male flies used for priming, possibly reflecting dosage effects (older flies produce lower emissions). Priming by younger males significantly reduced galling success, while priming by older males slightly improved it. Remarkably, female flies accurately assessed host‐plant quality by avoiding plants primed by young males while preferring those primed by older males. Synthesis . Our results suggest that defence priming in S. altissima in response to the volatile emissions of E. solidaginis males does affect fly fitness; however, the effect of priming varied by plant genotype, suggesting that there may be variation in defensive strategies against the fly. Female flies have, in response to this defence, evolved a sophisticated ability to evaluate the quality of primed plants. Abstract : Eurosta solidaginis males emit a putative pheromone that is attractive to females. Exposure to E ‐conophthorin, the primary component of the pheromone, primes the defenses of E. solidaginis 's host plant Solidago altissima . Overall, plants exposed to the pheromone were protected from galling by E. solidaginis ; however, the effectiveness of the defence varied, and females preferred to oviposit on less protected plants.